THE EFFECT OF TAX PLANNING AND NET PROFIT MARGIN ON COMPANY VALUE IN THE ESTABLISHMENT COMPANY REGISTERED ON BEI YEAR 2016 - 2019 - Maulida Matondang; Fitriani Saragih (Proceeding International Seminar of Islamic Studies, 2022)
This study aims to determine the effect of tax planning and net profit margin on plantation companies listed on the Indonesia Stock Exchange in 2016 2019. This research is an associative type of research. The sampling technique was carried out using a purposive sampling technique. So that the sample obtained was 12 plantation companies listed on the IDX in 2016 - 2019 with a total of 48 observational data for 4 years of observation. The data collection technique used is documentation. The data analysis technique used in this study is multiple linear regression analysis with SPSS 26 software tools. The results of the tax planning research show that the t-count statistical test value is 2,237 which is greater than the t table of 2, 010 while the tax planning sig value of 0.031 is smaller than 0.05, this shows that tax planning has a positive and significant effect on firm value. The net profit margin shows the t-count statistical test value of 1.671 which is smaller than the t-table of 2.010 while the value of the sig net profit margin of 0.103 is greater than 0.050, this indicates that the net profit margin has no effect on firm value. The results of the research on tax planning and net profit margin together show that the calculated F statistic value of 7.040 is greater than the F table value of 3.200 while the sig value of 0.002 is smaller than 0.05, this indicates a significant influence between tax planning and net profit margin to firm value simultaneously.